Features of diffusion mixing in Mo/Si multilayers - Penkov, A.V.; Voronov, D.L.; Devizenko, A.Yu.; Ponomarenko, A.G.; Zubarev, E.N. (Functional Materials, 2005)
X-ray photoelectron spectroscopy, transmission electron microscopy, and and low-angle X-ray diffraction were used to investigate the diffusion intermixing in multilayer periodic Mo/Si coatings during manufacturing and heating at 340-380 ℃. It is shown that the mixed zones in the initial state consist of MoSi₂ silicide. Сharacter of mixed zones growth depends on the interface type (Si on Mo or Mo on Si). At initial stage of annealing, the activation energy of interdiffusion has been found to vary from 0.1 to 2.1 eV and from 0.7 to 2.1 eV for the 1-st and 2-nd interface type, respectively.